1999
DOI: 10.1136/adc.81.5.380
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of deafness in infancy

Abstract: Results-A targeted PCHI was found in 1.18/1000 neonates. The PPV of the ABR for confirming a targeted PCHI was 100% when the ABR threshold was > 80 dBnHL. Nine of 11 infants with this threshold had severe or profound permanent deafness. The delay from ABR to audiological certainty was about 1 month-diagnosis was confirmed around 3 months. There was uncertainty when the ABR was 40-80 dBnHL. The PPV was 60% and 8% when the ABR thresholds were 70 dBnHL and 50 dBnHL, respectively. 85 of 111 infants with ABR thresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 14 publications
0
51
1
1
Order By: Relevance
“…25,26 Although the majority of infants in the United States are now screened, several recent studies report children with less severe degrees of loss, such as UHL and MBHL, are not being identified at the expected prevalence. 2,22,[27][28][29] As noted in Table 1 In comparison, research findings in the literature reported prevalence estimates in newborns for UHL that ranged from between 0.8/1000 to 2.7/1000. 27,29 Only 1 study had published data on the prevalence of MBHL in newborns, reporting a prevalence of 0.36 28 (Table 1).…”
Section: Newborn Hearing Screeningmentioning
confidence: 88%
“…25,26 Although the majority of infants in the United States are now screened, several recent studies report children with less severe degrees of loss, such as UHL and MBHL, are not being identified at the expected prevalence. 2,22,[27][28][29] As noted in Table 1 In comparison, research findings in the literature reported prevalence estimates in newborns for UHL that ranged from between 0.8/1000 to 2.7/1000. 27,29 Only 1 study had published data on the prevalence of MBHL in newborns, reporting a prevalence of 0.36 28 (Table 1).…”
Section: Newborn Hearing Screeningmentioning
confidence: 88%
“…Changes were based on epidemiological data and screening results from the 1970s to 2002, when local implementations became centrally directed. [26][27][28][31][32][33][34][35] Throughout the 25 years reactive referrals were received from primary health care, from paediatric and ENT services, and also directly from parents. The IDT was undertaken as a universal infant hearing screen at 8 months of age, until 1996.…”
Section: Changes In the Programmes Of Early Screening And Identificationmentioning
confidence: 99%
“…However, the Whipps Cross University Hospital universal newborn hearing screen (UNHS) has been implemented as an audited service since 1992 predating the country-wide implementation of newborn hearing screening by more than a decade. [26][27][28][29][30] The available information has also been used to evaluate the current worth of the local SES. The necessity for a local evidence base to be available to inform local policy has been emphasised, 5 but there are concerns about the applicability of studies with a small population base to inform wider policy.…”
mentioning
confidence: 99%
“…Hearing impairment is one of the most common disorders at birth, i.e., about 0.1% newborns suffer from such disorders (Kennedy and McCann, 2004;Mehl and Thomson, 2002;Morton and Nance, 2006;Norton et al, 2000;Watkin and Baldwin, 1999;Wessex Universal Neonatal Hearing Screening Trial Group, 1998). Although early diagnosis and treatment of such disorders in neonates is highly effective for realization of linguistic competence and intellectual development (Yoshinaga-Itano et al, 1998), diagnostic accuracy during the initial neonatal period of the birth is low.…”
Section: Introductionmentioning
confidence: 99%